2015
DOI: 10.2147/ott.s78236
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 acts as a prognostic marker in gastric cancer and its role in cell migration and invasion

Abstract: MicroRNA (miRNA)-153 (miR-153) has been considered as a novel tumor-related miRNA and is found to be significantly deregulated in human cancers. In this study, we found that the expression levels of miR-153 were obviously lower in gastric cancer tissues than those in matched adjacent nontumor tissues. Otherwise, miR-153 was expressed at significantly lower levels in aggressive tumor tissues. Clinical association analysis indicated that low expression of miR-153 was prominently correlated with poor prognostic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
5
31
0
1
Order By: Relevance
“…miR-153 has recently been considered a crucial factor in tumor metastasis ( 12 , 15 , 20 ). However, the role of miR-153 in PDAC remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-153 has recently been considered a crucial factor in tumor metastasis ( 12 , 15 , 20 ). However, the role of miR-153 in PDAC remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-153 high: value of expression > the median value; miR-153 low: value of expression < the median value. The relative expression of miR-153 was shown as the fold difference relative to U6 ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 8 In recent years, an increased number of studies have indicated that miRNAs have crucial functions in specific cellular processes such as differentiation, morphogenesis, and tumorigenesis and that miRNAs may also be considered oncogenes or tumor suppressors. 9 13 …”
Section: Introductionmentioning
confidence: 99%
“…The importance of microRNAs (miRNAs) have been testified in ischemic ailments, including cerebral ischemia (Ouyang, Stary, Yang, & Giffard, 2013). MiR-153 is a concerned miRNA, which has been extensively researched in diverse illnesses (Cao, Lv, & Lv, 2015;Zhang et al, 2015). An interesting research discovered that miR-153 inhibition could guard neurons against ischemia/reperfusion injury in an oxygen-glucose deprivation and reoxygenation model through adjusting nuclear factor erythroid 2-related factor 2/heme oxygenase 1 signaling (Ji et al, 2017).…”
mentioning
confidence: 99%